Recurrent Peri-Clitoral Abscess with Positive Actinomyces turicensis Culture - Diana Palacios; Cristina Wallace Huff (Case Reports in Obstetrics and Gynecology)
A peri-clitoral abscess is a condition that is seldom encountered in practice and is found scarcely in the literature. The cause of spontaneous peri-clitoral abscess not associated with female circumcision/genital mutilation is generally unknown. Additionally, there have been no case reports of positive Actinomyces culture at the time of drainage of a peri-clitoral abscess. This case outlines a 42-year-old female with a spontaneous peri-clitoral abscess. The abscess was initially treated with incision and drainage (I&D) and antibiotics, but it later reoccurred necessitating a second I&D with bedside marsupialization and antibiotics targeted at Actinomyces, which grew on the culture after primary I&D.